Türk hukukunda terk sebebiyle boşanma - Kandil, Seher (My University, 2005)
Boşanma, hukuk sistemimizde zina, hayata kast, pek kötü veya onur kırıcı davranış, suç işleme veya haysiyetsiz hayat sürme, terk, akıl hastalığı olarak gösterilen özel sebeplere veya evlilik birliğinin temelden sarsılması, eşlerin anlaşması ve ortak hayatın yeniden kurulması genel sebeplerinden birine dayanarak talep edilebilmektedir. Eşlerden birinin ortak hayata son vermek üzere evlilik birliğinden doğan yükümlülüklerini yerine getirmemek maksadıyla diğerini terk etmesi veya haklı bir sebep olmaması durumunda ayrılık, en az altı ay sürmüş ise terk edilen eş, boşanma davası açabilir. Boşanma davası açıldığı esnada ayrılığın devam etmesi şartı aranır. Terk edilen eşin, evlilik birliğini devam ettirme hususundaki samimiyetinin anlaşılması amacıyla terk fiilinden itibaren dördüncü ayın sonunda, ortak konuta dönmesi hususunda terk eden eşe mahkeme kanalıyla ihtarda bulunması gerekir. Dört aylık bu süre asgari süre olup, mutlaktır. Yine bu ihtardan sonra eşin ortak konuta dönmesi için de iki aylık bir süre kendisine verilir. Bu süreler sonunda eş, konuta dönmüyor ise artık terk sebebiyle boşanma davası açılabilir. Yeni düzenleme ile kanunumuza girmiş olan terk etmiş sayılma durumunda da aynı süreler ve ihtar şartı geçerlidir. Türk Medeni Kanunu'nda yer alan terk sebebiyle boşanmanın da içinde yer aldığı özel boşanma sebeplerinin kaldırılması gerektiğine inanmaktayız. In our law system, a divorce suit may be brought to the court due to one of these private reasons; adultery, attempt against life, cruelty or serious insult, infamous crime or dishonorable conduct, wilfull desertion, insanity; or due to one of these general reasons; incompatibility, agreement on divorce of the spouses and re-establishing of the shared life. When one of the spouses abandon the other in order to give an end to their shared life for the purpose of not fulfilling his/ her responsibilities stemming from the matrimonial union, the abandoned spouse may bring a divorce suit to the court if the abandonment has lasted at least for six months or if there is no rigtful reason. The abandonment should be on continuation at the time of sueing. At the end of the fourth month following the action of abandonment, the abandoned spouse should send a written warning statement via the court to warn the other spouse to return to the shared residence, in order to make clear that the abandoned spouse is sincere about keeping the matrimonial union. This period of four months is the minimum period, and is absolute. After this written warning, the other spouse is given a period of two months to return to the shared residence. If the abandoning spouse does not return to the shared residence after these periods, a divorce suit due to abandonment may be brought to the court. For the case of being the abandoning spouse, which is a new addition to the civil code with the latest amendments, the same periods and the condition relating the written warning is effective. We believe that, including divorce on abandonment, the private reasons for divorce, which are stil in effect through Turkish Civil Code, should be abolished.
Keywords: Özel Hukuk